The Relationship between Hypertension and the Risk of Falls in the Elderly - Jumratul Maisura; Bayhakki Bayhakki; Syeptri Agiani Putri (Journal of Education Technology Information Social Sciences and Health, 2024)
Increasing age will result in changes that occur, one of which is a decline in the cardiovascular system, especially hypertension. Hypertension that lasts a long time and if not treated properly will cause damage to the blood vessels in the heart. Damage to the heart's blood vessels will cause blood flow to the heart muscles to be obstructed. This can cause a heart attack which will increase the risk of falls. The aim of this study was to determine whether there is a relationship between hypertension and the risk of falls in the elderly. The design used is descriptive correlation and a cross sectional approach. The research sample was 82 respondents in the work area of the Rejosari Health Center, Pekanbaru City. using purposive sampling technique. The analysis used is the chi-square test. Based on the results of statistical tests, it shows that there is a relationship between hypertension and the risk of falls in the elderly, with P Value (0.001) alpha (0.05). Based on the results obtained, it was concluded that high blood pressure could result in a risk of falls in the elderly.